Estimasi Biaya Kepemilikan dan Biaya Operasi Pengupasan Tanah Penutup Berdasarkan Target Produksi PT MIFA Bersaudara Kecamatan Meurebo, Kabupaten Aceh Barat - Anjas Asmoro (Journal of Geosciences, Mining Engineering, and Technology, 2022)
Estimating the cost of ownership and operating costs incurred in operating a miningequipment is essential to see the equipment’s capabilities. This research aims tocompare the ownership and operating costs of stripping PT Mifa Bersaudaraoverburden with the cost of hourly equipment rental based on the employmentcontract of the contractor. This study resulted in a large cost calculation, hourlycost, and cost per BCM imposed on equipments when OB removal equipmentactivities and also support equipment work in October to December 2017. Owningcost per hour was US $ 523.84, of the cost of depreciation, interest, taxes, insurance,and storage, for an hourly operating cost of US $ 2,697.10, consisting of fuel, oiland grease, tire, maintenance and special items. Total owning costs and operatingcosts in October, November and December were respectively US $ 1,133,768.72-,US $ 1,053,245.37-, and US $ 953,396.42, and cost per BCM of US $ 1.49- , US $1.42-, and US $ 1.42- ,. In this research, the owning cost and operating cost iscompared with the operational cost obtained based on the hourly cost of equipmentrental at BCM cost in October of US $ 2.35-, November US $ 2.25-, and DecemberUS $ 2.25-. So as to produce the difference in cost per BCM in October US $ 0.86-, November US $ 0.82-, and December US $ 0.82-.